Sub Carrier Analysis for QAM Modulation - S. Shanmugasundaram (Institute of Advanced Engineering and Science, 2017)
Orthogonal Frequency Division Multiplexing (OFDM) based wireless data transmission system is a multi-carrier system in which single higher rate data stream can be divided into multiple lower rate data streams. Modulation and De-Modulation technique play a major role in OFDM based data transmission system. Based on Modulation technique only, the frequency transformation method and encoding and decoding methods are enabled. Effective modulation techniques called as “Quadrature Amplitude Modulation (QAM)” modulation are used to design an OFDM System. Carrier signal is one of the important signals used to modulate the original signal. Analyzing the sub-carrier signal for getting the quality of the modulated signal.